PENGARUH KENAIKAN SUHU PERMUKAAN LAUT TERHADAP ZONA POTENSIAL PENANGKAPAN IKAN CAKALANG DI PERAIRAN SELAT MAKASSAR - Safruddin; Abudarda, Andi Risda Fitrianti; Zainuddin, Mukti (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Makassar Strait plays a vital role as one of the skipjack tuna fishing grounds in Indonesia. This study aimed to detect the skipjack tuna preference of sea surface temperature (SST) and chlorophyll-a (Chl-a) in Makassar Strait and to map out the possible shifting potential fishing zone (PFZ) of skipjack tuna by simulating sea surface temperature increase. We analyzed the skipjack catch data from July to November 2020, and we added the previous data in June, July, August, October, and December 2019 in the same study area. We analyzed together with satellite imagery data set of SST and Chl-a using GAM. We used three scenarios for the SST increase model simulation, which are 0.25, 0.5, and 1℃. The results showed that skipjack tuna is relatively high in SST ranging from 28.3 to 30.4°C and Chl-a ranging from 0.18 to 0.28 mg/m3. The PFZ based on sea surface temperature simulation showed that PFZ area form in the northern part shifting to the southern part of Makassar Strait based on the increasing sea surface temperature simulation visible in September, which shifted from 0.017-5.421⁰S to 2.923-6.802⁰S and October shifted from 0.017-6.802⁰S to 5.007-6.802⁰S. Knowing the shifting of the potential fishing zone of skipjack tuna could be an important step toward fishing operation and management for skipjack tuna resource management in Makassar Strait.